Evolvable, sustainable low power optical network architectures - PAYNE, DAVID (Optical Society of America, 2011)
Optical communications technology offers an opportunity for radical restructuring future telecommunications networks. The major challenges for future networks with fibre to the premises (FTTP) is; economic viability, resource sustainability, the ability to evolve and adapt to new technologies with out large scale uplifts, particularly of the physical layer infrastructure, and also be able to accommodate a wide range of operating and business models. This tutorial will examine these issues and possible network architectural solutions that offer potential economic viability, substantial reductions in resource usage, particularly power consumption, and the ability to evolve as new technologies emerge in the future. Presenter Bio (100 Word Limit): David joined BT labs in 1978 working on single-mode splicing, connectors, fibre couplers and FTTP. In 1982 he started work on shared access networks leading to co-inventing TPON the first PON. This work extended to amplified PONs and an experimental 50 million split, 500km, 16x2.5Gb/s wavelength PON in 1991. In 1995 he moved into business/traffic modelling examining drivers/economics for FTTP.
PUBLISHED
Keywords: Telecommunications; FTTP